1983
DOI: 10.1063/1.94528
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy study of the surface chemistry of freon-oxygen plasma etched silicon

Abstract: X-ray photoelectron spectroscopy has been used to study residual film formation on silicon exposed to an oxygen-containing CF4 plasma. Experimental results indicate that the plasma reaction produces a surface phase SixOFy, which varies in thickness with the O content of the plasma. Film thickness is shown to correlate with the previously observed etch rate dependence on oxygen content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…This is higher in binding energy than Si in tetrahedral bond with O and is probably due to OF bonds as observed earlier by Thomas and Maa in residue layers on CFJO2 etched silicon (35). The peak due to the residue layer occurs at approximately 104 eV.…”
Section: Resultssupporting
confidence: 59%
“…This is higher in binding energy than Si in tetrahedral bond with O and is probably due to OF bonds as observed earlier by Thomas and Maa in residue layers on CFJO2 etched silicon (35). The peak due to the residue layer occurs at approximately 104 eV.…”
Section: Resultssupporting
confidence: 59%
“…This peak cannot be assigned to Li 2 CO 3 as the binding energy of this component is not in good agreement with that of Li 2 CO 3 and the two contributions of lithium alkyl carbonates, and there are not enough oxidized carbon atoms to account for all of the oxygen atoms in the form of carbonates. As the O 1s binding energies of metal oxyfluoride species such as Al−O−F (∼532.7 eV) and Si x OF y (532.9 eV) are close to 532.8 eV, the formation of (OH) y PF x like species such as (OH)PF 4 , (OH) 2 PF 3 , (OH) 3 PF 2 , or (OH) 4 PF is likely to occur on the surface of the cycled coated electrodes. However, based on the surface composition analysis, (OH) 2 PF 3 appears to be the most likely candidate.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15] In the fluorocarbon high density plasma, however, it has not been confirmed whether this process proceeds effectively because of the difference in the plasma chemistry. Recently, it was reported that the SiO 2 /photoresist etching selectivity could be improved by the addition of oxygen to C 4 F 8 ECR plasma.…”
Section: Introductionmentioning
confidence: 90%